Analisis multitemporal de la erosión producida por la explotación minera a cielo abierto en Soacha, Cundinamarca (2023)
Mining activity has currently been considered one of the most worked by human beings and whose process brings with it a significant relationship between time, space and society, but also the environment environment because its high demand has caused exploitation of substances that have as consequence worrying damage and erosion of the territories. This research performs an analysis of the erosion produced from 1990 to 2021 in the Municipality of Soacha due to the use of open pit mining, since this has been an activity that brings with it great changes at the infrastructure level, but a significant impact on the environment due to the exploitation of its mineral resources.